Postmetaphysics A Socio-Philosophical Challenge to the Indian Religious Public Sphere - Babu Suthi, Anil (Wissenschaftliche Buchgesellschaft (wbg), 2022)
Habermas' concept of postmetaphysics does orient us to engage in a dialogue between faith and knowledge that paves way to engage in a discourse concerning religion in public sphere. This thesis reconstructs socio-philosophical religious traditions, whose aim is to provide a discursive methodology in treating non-reflective expressions of religion.